Primary ovarian carcinoid tumor. Case report - Valencia-West, Angela (2020)
Primary neuroendocrine tumors are rare. They belong to a group of heterogeneous neoplasms that express similar immunohistochemical markers. Carcinoid tumors are the most common neuroendocrine neoplasms. Most of them arise in the gastrointestinal and bronchopulmonary tract. Primary carcinoid tumors of the ovary are rare entities that represent approximately 0.3% of all carcinoid tumors and less than 0.1% of all ovarian neoplasms, with good prognosis and generally limited to the ovarian parenchyma. These tumors arise from the ovarian stromal neuroendocrine cell system, superficial epithelium, and teratomas. In most cases, clinical manifestations are associated with the release of vasoactive substances that cause symptoms such as skin redness, diarrhea, and bronchospasm. For diagnosis it is necessary to use multimodal radiological images and biochemical analysis of neuroendocrine tumor markers. First-line treatment is tumor resection whenever possible. Prognosis is generally favorable, except in some cases with metastases. A case of primary ovarian carcinoid tumor is presented.